Antacids may increase the appearance of white opaque substance in Helicobacter pylori-eradicated gastric epithelial neoplasia - Wada, Kurato; Ueo, Tetsuya; Yonemasu, Hirotoshi; Togo, Kazumi; Inoue, Shotaro; Honda, Hideho; Katsuta, Makoto; Takahashi, Haruhiko; Yao, Kenshi; Murakami, Kazunari (Endoscopy International Open, 2019)
Background and study aims White opaque substance (WOS) in gastric epithelial neoplasia is helpful for qualitative diagnosis of neoplasia. We hypothesized that WOS of neoplasia is strongly influenced by acid recovery after Helicobacter pylori eradication, similar to that of gastric intestinal metaplasia. The aim of this study was to investigate whether antacids increase the appearance of the WOS in H. pylori-eradicated neoplasia.Patients and methods A total of 38 gastric epithelial neoplasias (12 adenomas and 26 adenocarcinomas) detected after H. pylori eradication were retrospectively evaluated. Presence or absence of WOS was evaluated by magnifying endoscopy with narrow band imaging before and after antacid administration. The pH of collected gastric juice was also measured. Study endpoints were (1) prevalence of WOS in the neoplasia before and after antacid administration, and the histological difference (adenoma and adenocarcinoma); and (2) relationship between the prevalence of WOS and gastric juice pH.Results WOS prevalence increased from 0 % (0/38) to 44.8% (17/38) after antacid administration. WOS prevalence in adenomas was more significantly increased compared to that in adenocarcinomas (83.3 % vs 26.9 %, P = 0.0077). Prevalence of WOS in gastric neoplasias was only observed at neutral levels of gastric juice pH, and WOS was not observed at strong acidic levels.Conclusions Antacid administration may increase the appearance of WOS in gastric epithelial neoplasia (especially adenomas) detected after H. pylori eradication with acid recovery.